Development of a Post-Traumatic Growth Model in Women Affected by Marital Infidelity Based on Differentiation of Self: The Mediating Role of Behavioral Emotion Regulation - Moazzezi, Mehraz; Peymani, Javid; Dartaj, Fariborz (International Journal of Education and Cognitive Sciences, 2026)
Purpose: The present study aimed to develop and test a structural model of post-traumatic growth in women affected by marital infidelity based on differentiation of self, with the mediating role of behavioral emotion regulation.Methods and Materials: This study employed a descriptive-correlational design using structural equation modeling (SEM). The statistical population consisted of women who had experienced marital infidelity and sought services from licensed counseling and psychotherapy centers in District 5 of Tehran during the first quarter of 2025. Based on the recommendation of Tabachnick and Fidell (2007), a sample of 300 participants was selected through convenience sampling. Data were collected using the Posttraumatic Growth Inventory (PTGI) developed by Tedeschi and Calhoun (1996), the Differentiation of Self Inventory developed by Skowron and Friedlander (1998), and the Behavioral Emotion Regulation Questionnaire developed by Kraaij and Garnefski (2019). Data analysis was conducted using SmartPLS version 3, and direct and indirect relationships among the study variables were examined through path analysis.Findings: The structural model demonstrated several significant direct and indirect relationships between dimensions of differentiation of self, behavioral emotion regulation, and post-traumatic growth. Emotional reactivity, as a component of differentiation of self, showed a significant positive direct relationship with post-traumatic growth (β = 0.14). Regarding indirect effects, emotional reactivity was negatively associated with post-traumatic growth through social support seeking (β = -0.09). Emotional cutoff exhibited significant negative indirect relationships with post-traumatic growth through active approach (β = -0.05), ignoring (β = -0.06), distraction (β = -0.06), and withdrawal (β = -0.05). In contrast, emotional fusion demonstrated a significant positive indirect relationship with post-traumatic growth through withdrawal (β = 0.05).Conclusion: The findings indicate that differentiation of self contributes significantly to post-traumatic growth both directly and indirectly through behavioral emotion regulation strategies. Behavioral emotion regulation serves as an important psychological mechanism through which self-differentiation influences adaptation and positive psychological growth following the trauma of marital infidelity.